Air pollution monitoring through the application of atmospheric correction for ASTER imagery - Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2009)
This paper presents the results obtained through the application of atmospheric correction on ASTER images for deriving the aerosol optical thickness (AOT). The literature shows that there is a gap in correlating the determined or measured AOT through the visible and near-infrared spectrum with the air-pollutants such as PM10, PM2.5, CO2, etc. This research investigates such aspects by acquiring sun-photometer measurements, image data, and air-pollutants measurements during the satellite overpass of the urban areas in Paphos and Limassol District in Cyprus. AOT values delivered from MODIS satellite images are regressed against the sun-photometer ground-based measurements. The determined AOT values from both sources are compared with the AOT values retrieved from ASTER and/or LANDSAT TM /ETM+ images. Preliminary results show that the AOT retrieved after applying an atmospheric correction from the images was very near to those found from the sun-photometers acquired simultaneous during the satellite overpass
Keywords: Air quality; Atmospheric aerosols; Atmospherics; Environmental engineering; Geographic information systems; Geology; Infrared spectroscopy; Photometry; Radiometers; Remote sensing; Satellites; Sun